Influence of wolf predation on population momentum of the Nushagak Peninsula caribou herd, southwestern Alaska - Walsh, Patrick; Woolington, James (Rangifer, 2019)
We investigated wolf predation as a potential driver of population change in the Nushagak Peninsula caribou herd, southwestern Alaska. We investigated the time budgets of three wolf packs using the peninsula from 2007 through 2012, and thus potentially preying on caribou there, in order to make inferences on their likelihood of serving as an important population modifier for the Nushagak Peninsula caribou herd. We found that only one pack regularly used the peninsula. The pack using the peninsula spent an average of 35% of its time there. Its use of the peninsula was disproportionately high in late summer and fall, disproportionately low in winter, and proportional during the caribou calving season in early summer. Overall wolf use of the Nushagak Peninsula increased in direct response to increasing caribou abundance but was not a primary population driver.